Divulgação das geociências e da universidade pública para estudantes da rede de ensino de Apiaí (SP) - Pimentel, Giovana Oliveira [UNESP]; Farias, Vanderlei [UNESP]; Teixeira, Wallace Soares [UNESP]; Ramponi, Frederico Figueiredo [UNESP]; Rechtenthal, Felipe Unterrichter [UNESP]; Leite Junior, Washington Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Geology PET Group of UNESP did in Apiaí (SP), Ribeira Valley region, activities with students of elementary school, high school and technical school, intending to propagate the geosciences for population of the region with one of the lowest HDI of São Paulo. Introduce the public university and stimulate ingress interest to higher education were other objectives. Different approaches have been made according to the education level of the class and was noted interest and participation by the students mainly during the practical activities involving minerals and rocks and products of dayto-day extracted from them.

O Grupo PET Geologia da UNESP realizou em Apiaí (SP), região do Vale do Ribeira, atividades com alunos do Ensino Fundamental, Médio e Técnico, visando divulgar as Geociências à população da região com um dos menores IDH do estado de São Paulo (PNUD, 2013). Apresentar a universidade pública e estimular o interesse de ingresso ao nível superior foram outros objetivos propostos. Diferentes abordagens foram feitas de acordo com a escolaridade da turma e notou-se interesse e participação por parte dos alunos principalmente durante as atividades práticas envolvendo minerais e rochas e os produtos do dia-a-dia deles extraídos.
Keywords: Propagation; Geoscience; Ribeira Valley; Divulgação; Geociências; Vale do Ribeira